2020
DOI: 10.3389/fneur.2020.593524
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Vertigo Attack Frequency as a Predictor of Ischemic Stroke

Abstract: Background: Recurrent attacks of vertigo account for 2.6 million emergency department visits per year in the USA, of which more than 4% are attributable to ischemic infarction. However, few studies have investigated the frequency of attacks of vertigo before an ischemic stroke.Methods: We conducted this retrospective analysis and manually screened the medical records of 231 patients who experienced recurrent attacks of vertigo prior to an ischemic stroke. Patients were divided into four different groups based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These results agree with those of Elhfnawy et al [ 51 ] who, in their study, found that there were fewer patients with associated neurological deficits in the vertigo group. We must differentiate our work from the interesting study published by Qiu et al [ 71 ]. In their study, previous vertigo attacks were a risk factor or predictor of the presence of posterior acute ischemic stroke, whereas, in our study, vertigo and labyrinthine symptoms are clinical symptoms present at the onset of stroke in all patients analyzed.…”
Section: Discussionmentioning
confidence: 97%
“…These results agree with those of Elhfnawy et al [ 51 ] who, in their study, found that there were fewer patients with associated neurological deficits in the vertigo group. We must differentiate our work from the interesting study published by Qiu et al [ 71 ]. In their study, previous vertigo attacks were a risk factor or predictor of the presence of posterior acute ischemic stroke, whereas, in our study, vertigo and labyrinthine symptoms are clinical symptoms present at the onset of stroke in all patients analyzed.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, the importance of accurately assessing ischemic stroke in the posterior circulation is highlighted, and the utility of symptoms is emphasized [ 4 ]. Vertigo is a common complaint in the clinic with a high risk of recurrence [ 5 , 6 ]. According to the epidemiological survey, vertigo is one of the most common symptoms of POCI, occurring in 47%–75% of posterior circulation stroke patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These accompanying neurological deficits were observed in 11% of patients with vertebrobasilar ischemic stroke ( 7 , 8 ). As stroke is the leading cause of severe disability, failure to recognize focal deficits prior to vertebrobasilar stroke may result in worse outcomes ( 9 , 10 ). Thus, highlighting the differences in patients with vertigo attacks only and vertigo accompanying weakness attacks is important for secondary stroke prevention.…”
Section: Introductionmentioning
confidence: 99%